DEBITTERING OF Borassus flabellifer MESOCARP USING NARINGINASE: IMPACT ON THE COMPOSITION, PHYSICOCHEMICAL CHARACTERISTICS, AND FUNCTIONAL PROPERTIES - HASSAN, RODIAH BINTI; Bakar, Jamilah; Hussain, Norhayati; Muhamad , Kharidah (Malaysian Journal of Science, 2023)
This study explores the physicochemical, composition, and functional properties of the Borassus flabellifer mesocarp powder following treatment with naringinase. The debittered mesocarp powder (DMP) has good water-holding (9.4 g/g), swelling (7.8 g/g), and wettability (12.3 s) capacities. Naringinase reduced 33.2% of the DMP particle size, causing an increase in surface area. A larger surface area traps more water/oil molecules, contributing to a higher water/oil capacity. However, the solubility, swelling, and wettability of DMP were markedly decreased following naringinase treatment. Nonetheless, although DMP has higher saponin, phenol, tannin, and DPPH activity contents than the control, it has decreased ferrous-reducing activity.